TURKISH VERSION OF BODY AWARENESS QUESTIONNAIRE: VALIDITY AND RELIABILITY STUDY - KARACA, SEDA (TURKEY ASSOC PHYSIOTHERAPISTS, 2021)
Purpose: The Body Awareness Questionnaire (BAQ) was described as a tool with psychometric properties that thoroughly assessed the concept of body awareness. There is no Turkish version of the scale with validity and reliability. The study aimed to demonstrate the validity and reliability of the Turkish version of the BAQ. Methods: The study sample consisted of 180 university students (age=21.87 +/- 2.36 years, 99 M, 81 F). The BAQ, Self-Consciousness Scale (SCS), and Body Cathexis Scale (BCS) were applied to the participants. Results: Result of the correlation analysis between the BAQ and the total scores obtained from the SCS and BCS, and the correlation coefficients were determined as 0.802 (p=0.007) and -0.753 (p=0.009), respectively. As a result of the explanatory factor analysis, a measurement tool consisting of 18 items and four sub-groups explaining 66% of the variance was obtained. The test retest reliability coefficient was 0.830 at 3-day intervals. Cronbach's alpha was calculated as 0.917 to determine internal consistency. Conclusion: Findings in the study show that the Turkish version of BAQ is valid and reliable.
Keywords: Body Awareness; Reliability; Turkish; Validity; SELF-CONSCIOUSNESS; THERAPY; PRIVATE